Lupins in the genome editing era: advances in plant cell culture, double haploid technology and genetic transformation for crop improvement - Pathi, Krishna Mohan; Sprink, Thorben (Frontiers in Plant Science, 2025)
The global trend towards plant-based protein sources as an alternative to animal-derived protein has surged due to health benefits, rising adoption of vegan and vegetarian lifestyles. This shift promotes sustainable agriculture by mitigating greenhouse gas emissions and safeguarding biodiversity. Among various plant-based protein sources, legumes have received considerable attention due to their high-protein content, gluten-free nature and nitrogen-fixing capacity, making them indispensable in crop rotation systems. Within the legume family, lupins are gaining global attention for their exceptional nutritional profile and bioactive compounds with promising health benefits. Although lupins offer significant nutritional benefits, challenges such as biotic and abiotic stresses and anti-nutritional factors persist. Addressing these challenges demands advanced breeding techniques capable of mitigating these issues without compromising desirable traits. Genome editing holds promise for enhancing crop traits, including improved nutritional value and resistance to environmental stresses. The availability of complete genome sequences for lupin species provides a foundation for genome editing and accelerated breeding. However, genome editing requires reproducible plant cell culture and transformation protocols. Nonetheless, legumes exhibit a high degree of recalcitrance to in vitro regeneration and genetic transformation, the underlying mechanisms of which remain largely unknown. This review provides a comprehensive examination of the current advancements, challenges and future prospects associated with plant cell culture, genetic transformation, genome editing and double haploid (DH) technologies in the context of lupin improvement. Additionally, this review briefly discusses major obstacles in conventional lupin breeding.